2022-RA-898-ESGO Overexpression of TMED9 is important prognostic biomarker for epithelial ovarian cancer. (20th October 2022) - Kim, Hyosun; Han, Gwan Hee; Yun, Hee; Chung, Joon-Yong; Kim, Jae-Hoon; Cho, Hanbyoul
Abstract : Introduction/Background: Transmembrane emp24 domain-containing protein 9 (TMED9) belongs to the TMED/p24 family which regulates the innate immune and protein transport via the ER-Golgi cargo pathway. Previous studies have reported that high expression of TMED9 contributes to diseases such as cancer. However, its role in epithelial ovarian cancer (EOC) has not been clarified yet. Therefore, we aim to evaluate the function, molecular mechanism, and clinicopathological significance of TMED9 in EOC. Methodology: The expression level of TMED9 was screened by RNA sequencing of 10 EOCs and normal epithelial ovarian tissues. Expression of TMED9 was respectively evaluated by Immunohistochemistry staining of EOC, borderline, benign, and normal epithelial tissues, qPCR, western blotting, and public data sets. Associations of clinicopathological features and prognosis with TMED9 in EOC patients were analyzed in our recruited cohort and GEO datasets. Also, the functional roles of TMED9 were evaluated by MTS, colony formation, and transwell migration/invasion assays in EOC cell lines. Results: TMED protein was elevated in EOCs according to a GEO and TCGA datasets. High mRNA and protein levels of TMED9 were observed in EOCs compared to borderline, benign, and normal nonadjacent ovarian epithelial tissues ( p < 0.001). Importantly, high expression of TMED9 was associated with poor overall survival and disease-free survival compared with low expression of TMED0 in EOCs ( p = 0.006, p < 0.001). In vitro results also demonstrated the knockdown of TMED9 was associated with decreased cell invasion (p < 0.001), migration ( p < 0.001), proliferation ( p < 0.001), and colony-forming abilities ( p < 0.001) supporting the oncogenic role in EOC. Conclusion: Our study is the first work to identify an oncogenic role of TMEd9 in EOC tissues and cell lines which may provide insights into the application of TMED9 as a novel predictor of clinical outcome and a potential therapeutic target in EOC patients.